Physico-chemical stability evaluation of a sedimentary agglomerates use for the coastal protection - Zadi, Louis; Turcry, Philippe; Soive, Anthony; Zanibellato, Alaric; Mahieux, Pierre-Yves; Sabot, René; Jeannin, Marc (Journal of coastal conservation, 2023)
The stability of sedimentary aggregate used for the stabilization of dykes in coastal area is investigated. This material is formed by cathodic polarization in seawater and is composed of marine sediments and calcareous deposit (brucite ( M g ( O H ) 2 ) and aragonite ( C a C O 3 )). Once the electrical current is switched off, this material could be subject to physical and mineralogical evolution, which may threaten the integrity of the protected structures. Few studies have been done on the pure calcareous deposit but not on this agglomerate, which is the major point of this study. For this purpose, 5 materials formed in laboratory were immersed during 18 months in natural seawater in the absence of electric current. Porosity and mineralogical composition (XRD and TGA/DTG) analyses were carried out at different times and an accelerated test was set up to evaluate a longer behavior of these aggregates. As the pure calcareous deposit, the ageing of these materials is characterized by a dissolution of brucite favoring the precipitation of aragonite. Contrary to thermodynamic expectations, this transformation takes place with a molar yield of less than 0.5 during the first 6 months of immersion. This implies a loss of material during this period, which is however slowed down in time by the local precipitation of aragonite and limits the dissolution reactions. Moreover, the mass ratio of these two phases ( M g ( O H ) 2 / C a C O 3 ) is stable in the vicinity of 18 months of abandonment in natural seawater with a very low porosity variation (lower than 10%), which is an indication of this material stability.